2020
DOI: 10.1002/gj.3744
|View full text |Cite
|
Sign up to set email alerts
|

Late Cenozoic magnetostratigraphy of the Yuncheng Basin, central North China Craton and its tectonic implications

Abstract: Yuncheng Basin, the southernmost basin in the Shanxi Graben System, is considered to be one of the earliest formed in this region. However, due to the insufficient study on the strata and the lack of drilling data, the initial time of the Yuncheng Basin has not been accurately constrained, which heavily restricts our understanding about the formation and evolution of the Shanxi Graben System. In this study, borehole SG-1, which penetrated through the entire Late Cenozoic sediments and reached the basement bedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(86 reference statements)
1
11
0
Order By: Relevance
“…The hangingwall block is a tilted block, dipping toward south and producing a depocenter close to the NZTF. This is highlighted by the thickening of basin fill deposits moving from north (few hundred meters) to south (more than 5000 m), as testified by drilling and geophysical data [25,40] ( Figure 2B).…”
Section: Background Settingmentioning
confidence: 75%
See 4 more Smart Citations
“…The hangingwall block is a tilted block, dipping toward south and producing a depocenter close to the NZTF. This is highlighted by the thickening of basin fill deposits moving from north (few hundred meters) to south (more than 5000 m), as testified by drilling and geophysical data [25,40] ( Figure 2B).…”
Section: Background Settingmentioning
confidence: 75%
“…Previous results from geology, seismicity, and geodesy investigations indicated that the graben systems were developed under a regional extensional stress field and characterized by the fault-uplift side of ranges and the subsidence of basins [29][30][31][32]. In addition, the ranges and basins are controlled by active normal faults and show the mirror image symmetry [25,28,32,33].…”
Section: Background Settingmentioning
confidence: 99%
See 3 more Smart Citations